Análise metabolômica via RMN: amostras de urina e látex - Nascimento, Eduardo Sanches Pereira do (Universidade Federal de São Carlos, 2011)
The aim of the first part of this work was to apply the concept of metabolomic analyses in urine samples obtained from humans diagnosed with type 2 diabetes mellitus (T2DM) and impaired glucose tolerance (IGT) and treated with yerba-mate (Ilex paraguariensis) infusions using nuclear magnetic resonance. T2DM is the most recurrent type of diabetes and corresponds to about 85-90% of DM cases. Brazil is the fifth country with the largest number of people diagnosed with DM and it was estimated that in 2010 about 40 thousand people died due to diabetes. Yerba-mate (Ilex paraguariensis) is a tree which belongs to the family aquifoliaceas and it is originated from the subtropical region of South America. Among several phytochemicals present in yerba-mate the most important are phenolic compounds, saponins and methylxanthines. The use of yerba-mate as a functional food is relatively recent and earlier studies have shown that aqueous extracts of Ilex paraguariensis, which are rich in phenolic compounds, are capable of inhibit the formation of the advanced glycation end-products. Nuclear magnetic resonance (1H NMR and two-dimensional experiments) was capable of identify and quantify the major metabolites present in the human urine samples diagnosed with T2DM and IGT. The relatively quantification of the metabolites alanine, DMA, citrate, creatinine, betaína and TMAO showed that the intake of yerba-mate infusions could assist in the treatment of DM. The aim of the second part of this work was to apply the concept of metabolomic analyses in latex samples using the nuclear magnetic resonance technique as an analytical tool to evaluate the influence of rootstock on grafting, the quality of latex from different Abstract xiv DQ - UFSCar rubber tree clones and the latex with high and low production of poliisoprene belonging to the same clone. The production and consumption of natural rubber in Brazil is gradually growing, however the consumption rate is superior to the production rate causing deficits and rising imports of the product. The rubber tree clones in Brazil were created and studied in order to fight South America Leaf Blight, however the focus of recent works have been the developments of clones with high poliisoprene production, wind resistance, better precocity, and panel disease resistance. Nuclear magnetic resonance (1H NMR and two-dimensional experiments) was capable of identify and quantify the major metabolites present in the latex samples. In the study of the influence of rootstock on grafting was possible to distinguish the latex samples from the RR and GG groups. The latex samples from GR group are similar to the latex samples of RR group while the latex samples of RG group are spread between the RR and GG groups. From the several clones studied in this work it was possible to verify that the IAC 505 clone is the most similar to the experiment witness clone RIMM 600. Through the analysis of the 1H NMR spectrum of the IAC 235 latex samples was possible to verify that the most important difference between the latex samples with high and low production of poliisoprene is the concentration of sucrose.
Metabolomic analyses by NMR: urine and latex samples
Keywords: Ressonância magnética nuclear; Quimiometria; Diabetes mellitus; Erva-mate; Seringueira; Clones; CIENCIAS EXATAS E DA TERRA::QUIMICA